1988
DOI: 10.1172/jci113442
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes expressing type 3 complement receptors proliferate in response to interleukin 2 and are the precursors of lymphokine-activated killer cells.

Abstract: In the absence of antigenic or mitogenic stimulation, certain peripheral blood lymphocytes exhibit proliferative and lymphokine-activated killer (LAK) cell activities when cultured with recombinant IL-2. Both activities were found to be an exclusive property of lymphocytes expressing type 3 complement receptors (CR3) identified by anti-CD1 1 monoclonal antibodies. CD11+ lymphocytes were then fractionated into three subsets by two-color flow cytometry. These included CD16+ cells, which display distinctive Fc re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…NK cells are normally present in the circulation and, along with other populations of lymphocytes, are further activated by the T-cell lymphokine interleukin 2 (IL-2) (4)(5)(6)(7)(8)(9). These so-called lymphokine-activated killer cells, or LAK cells, display a greater lytic capacity and recognize a broader range of target cells than their nonactivated counterparts (6)(7)(8)(9). Despite these presumably capable killer cells, humans are frequently afflicted with cancer and with persistent or recurrent viral infections.…”
mentioning
confidence: 99%
“…NK cells are normally present in the circulation and, along with other populations of lymphocytes, are further activated by the T-cell lymphokine interleukin 2 (IL-2) (4)(5)(6)(7)(8)(9). These so-called lymphokine-activated killer cells, or LAK cells, display a greater lytic capacity and recognize a broader range of target cells than their nonactivated counterparts (6)(7)(8)(9). Despite these presumably capable killer cells, humans are frequently afflicted with cancer and with persistent or recurrent viral infections.…”
mentioning
confidence: 99%
“…The molecules responsible for C3 deposition under these conditions remain unidentified. Another report has suggested that C3 deposition physiologically occurs in damaged cells for facilitating clearance by C receptor-positive leukocytes (43)(44)(45)(46). In fact, P39 + sublines were established through culture in conditions under which most cells died (18).…”
Section: Discussionmentioning
confidence: 99%
“…The other possibility is that VSIG4 inhibits T cell activation by acting as a complement receptor. Despite the fact that the expression of C3 receptors CR1 and CR3 on T cells was described many years ago (11)(12)(13), the function of these receptors on T cells is unclear. However, a recent study demonstrated that cross-linking CR1 and CR3 with antibodies profoundly inhibits T cell proliferation (14).…”
Section: Dual Functions Reveal More Questions Than Answersmentioning
confidence: 99%